Morphologie du récit super-héroïque à l'épreuve de la transmédialité : du médium bédéique à la série, que sont nos héros devenus ? - Frédéric Aubrun; Vladimir Lifschutz (Cahiers de Narratologie)
This article analyzes the morphology of the superheroic narrative based on the contributions of Propp and Greimas in comic books, and in the transmedia adaptations of Batman and Watchmen into series centered on origin stories. The transmedia adaptive processes find in comic books numerous transposition possibilities, which the authors propose to study in the adaptation from comic books to TV series, through the prism of origin stories.